Design and construction of a motor-actuated sea ice compression testing machine - Keche, Tamuka (Department of Chemical Engineering, 2025)
This thesis investigates the mechanical properties of sea ice in the Southern Ocean's Marginal Ice Zone, with the main emphasis on developing a specialized sea ice compression testing machine. The machine, designed for harsh sub-zero and saline conditions, would facilitate the immediate testing of ice samples onboard the SA Agulhas II vessel. The research entailed designing and constructing a compression machine capable of exerting up to 50 kN of force and accommodating strain rates critical for studying sea ice compressive strength. Field tests were conducted using ice cores collected from the MIZ consolidated ice. Compression tests were performed at strain rates around 4 x 10-4/s, which falls within the ductile-to-brittle transition zone, where maximum ice compressive strength is expected. The tested samples exhibited ductile failure modes in ice cores, with maximum stress observed before a gradual stress relaxation. Notably, the maximum stress observed was 6.91 MPa, aligning with established literature values for the compressive strength of sea ice. Additionally, the thesis provided a detailed analysis of the elastic moduli of sea ice. Despite the machine's slight deformation under load, the results indicated elastic moduli within the literature-reported range for sea ice. This data is crucial for understanding sea ice's elastic properties under varying environmental conditions. In conclusion, the newly designed sea ice compression machine functioned effectively at - 10°C, withstanding up to 44 kN of force and testing across a range of strain rates. Despite minor elastic deformation, it accurately measured ice strength, aligning with established data and proving its robustness for future research. Recommendations for future research include enhancements to the machine's design for improved precision and adaptability in testing. The findings suggest potential areas for further investigation in sea ice mechanics, emphasizing the importance of continued exploration for broader climate science implications.